2023
DOI: 10.1039/d2ta09932b
|View full text |Cite
|
Sign up to set email alerts
|

Continuous and ultrafast MOF synthesis using droplet microfluidic nanoarchitectonics

Abstract: Metal-organic frameworks (MOFs) constitute a class of porous materials with widespread applications owing to their remarkable and tunable properties. Although MOFs are currently the leading examples of porous materials, they...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Unfortunately, the one-pot method has not yet developed into the most general method because of its long reaction time, strict reaction conditions, and unstable coordination patterns of organic ligands. 138…”
Section: Mofs and Mofs-based Catalystsmentioning
confidence: 99%
“…Unfortunately, the one-pot method has not yet developed into the most general method because of its long reaction time, strict reaction conditions, and unstable coordination patterns of organic ligands. 138…”
Section: Mofs and Mofs-based Catalystsmentioning
confidence: 99%
“…The results indicated that the segment flow microreactor allowed the fast synthesis (10 min) of ZIF-8 crystals with a narrow PSD, but the largest total flow rate was just 1.0 mL/min. Wu et al 35 adopted a continuous droplet microreactor to accelerate the generation of ZIF-8 and MIL-100, and the results indicated that the microreactor method could achieve crystallinity comparable to that using the traditional batch hydrothermal method while significantly reducing the residence time from 200 min to 24 s. However, the total flow rate was just 0.53 mL/min. In summary, the low throughput hindered the industrial applications of the ordered microreactors.…”
Section: Introductionmentioning
confidence: 99%
“…The microfluidic-based method is a cost-effective green process, [37] having favorable characteristics such as good mass and heat transfer effects, speeding up the growth rate of MOF in droplets, and reduced energy consumption and solvent usage. [38][39][40] Through the precise control of different reaction conditions, MOF with narrow size distribution and specific types can be synthesized, thereby achieving good reproducibility and production stability. [41][42] Among the microfluidic-based approach, continuous flow synthesis of the micro-droplet reaction system can quickly realize the efficiency of heat transfer and mass transfer in the droplet, improve the sensitivity of the product to the reaction parameters, and significantly reduce the use of precursor solutions.…”
Section: Introductionmentioning
confidence: 99%